Forest Zoning in the Peruvian Amazon: Strategies to mitigate its environmental impacts and strengthen environmental governance in Peru - Barboza Isla, Nicholas Gabriel; Minaya Loconi, Maritza Angeli; Velazco Bernal, Pierre Alexander; Murga Gonzalez, Iselli Josylin Nohely; Naupari Montenegro, Sara Rita (LACCEI, 2025)
Deforestation and forest degradation in the Peruvian Amazon have caused significant environmental impacts, affecting biodiversity, water resources, and soil stability. However, current legislation has gaps that limit the State's ability to effectively manage forest resources and mitigate these impacts. This study analyzes Law No. 31973, which amends Law No. 29763, the Forest and Wildlife Law, and approves complementary provisions aimed at forest zoning, comparing Peruvian environmental legislation with the regulations of other countries that have achieved effective forest management to identify best practices applicable to Peru. A systematic review of scientific literature and international legislation was conducted using databases such as Redalyc, Scopus, and Google Scholar, with keywords related to deforestation and environmental laws. The results showed that Law No. 31973 weakened forest management by eliminating land classification and restricting the State’s capacity to restore degraded areas. In contrast, Brazil, Guatemala, and Costa Rica have implemented effective strategies, such as economic incentives for conservation (PSA in Brazil, PINFOR in Guatemala), environmental monitoring (CAR in Brazil), and reforestation programs, while India and Sweden stand out for their focus on community participation and sustainable reforestation regulations. It is concluded that Peru could adapt these practices to close legal gaps and promote sustainable development, aligning itself with international commitments on sustainability and climate change, thus fostering responsible environmental management.